Application of the Rule Based Expert System Method against Brute Force Attacks Force Attack on Mikrotik Cloud PLN Icon Plus Medan Office - Reinaldo, Reinaldo; Hafni; Muttaqin, Muhammad (Cattleya Darmaya Fortuna, 2025)
In this research, the author discusses the application of the rule-base expert system method against brute-force attacks on the Mikrotik cloud. The author uses the rule base method to set rules on the Firewall that facilitate the verification and authentication process. The number of attacks on servers aimed at hunting down important data lately has made a very serious problem, especially in the makes a very serious problem, especially in Indonesia. Testing is done using an attack system with Linux times with the CLI destination on Mikrotik Cloud. The attack carried out uses a brute force attack. In this study, kali linux cannot enter the Mikrotik CLI system. Rule Base Expert System can block attacks on Mikrotik Cloud.